(untitled) (Research, Society and Development, 2020)
The movies constitute a valuable didactic resource in the Teaching of Natural Sciences in order to promote Scientific Literacy. However, the literature points out the difficulties found by teachers to use this resource in their classes. In this work we analyze the "Sammy’s Adventures" movies which aims to identify the potential content that can be addressed in science classes. The analysis of the film was carried out by two specialists in the field of Natural Sciences. This movie presents scenes with changes in the environment resulting from natural processes and phenomena and also by human intervention. Through the analysis of the film, it was possible to identify that several scenes converge with the knowledge objectives to be developed in the thematic units Matter and Energy and Life and Evolution of the Base Nacional Comum Curricular. This result highlights the potential of "Sammy’s Adventures" movies to be used in the teaching of Nature Science classes with students in the early years of elementary school, as well as to explore themes and emerging environmental problems.